COMPARATIVE ANALYSIS OF NAMING PRACTICES BETWEEN ENGLISH AND UZBEK CULTURES - Zebuniso Ramazonova (Journals Park Publishing, 2024)
The selection of names for people is a complex and multifaceted process that is influenced by a variety of cultural, social, and personal factors. This article explores the key motivations and considerations that guide the naming of individuals, drawing on relevant research and theoretical perspectives. Key themes discussed include the significance of names, the role of tradition and cultural identity, the influence of personal preferences and meanings, and the evolving nature of naming practices. The article provides a comprehensive overview of the topic, highlighting the importance of understanding the motivations behind name selection for various applications, such as in the fields of psychology, sociology, and anthropology.
Keywords: Name selection, personal identity, cultural traditions, meaning of names, naming practices